Myosin Light-Chain Kinase Is Necessary for Membrane Homeostasis in Cochlear Inner Hair Cells - Zhu, Guang-Jie; Wang, Fang; Chen, Chen; Xu, Lin; Zhang, Wen-Cheng; Fan, Chi; Peng, Ya-Jing; Chen, Jie; He, Wei-Qi; Guo, Shi-Ying; Zuo, Jian; Gao, Xia; et al. (PLOS ONE, 2012)
The structural homeostasis of the cochlear hair cell membrane is critical for all aspects of sensory transduction, but the regulation of its maintenance is not well understood. In this report, we analyzed the cochlear hair cells of mice with specific deletion of myosin light chain kinase (MLCK) in inner hair cells. MLCK-deficient mice showed impaired hearing, with a 5- to 14-dB rise in the auditory brainstem response (ABR) thresholds to clicks and tones of different frequencies and a significant decrease in the amplitude of the ABR waves. The mutant inner hair cells produced several ball-like structures around the hair bundles in vivo, indicating impaired membrane stability. Inner hair cells isolated from the knockout mice consistently displayed less resistance to hypoosmotic solution and less membrane F-actin. Myosin light-chain phosphorylation was also reduced in the mutated inner hair cells. Our results suggest that MLCK is necessary for maintaining the membrane stability of inner hair cells.